1981
DOI: 10.1093/clinchem/27.5.709
|View full text |Cite
|
Sign up to set email alerts
|

Albumin and beta 2-microglobulin radioimmunoassays applied to monitoring of renal-allograft function and in differentiating glomerular and tubular diseases.

Abstract: Blood and urine were samples daily from 11 renal-allograft recipients from one to six weeks after the transplant. Clearances of both albumin (Calb) and beta2-microglobulin (C beta 2 mu) were significantly increased in all 11 patients. Five patients (Group I) with acute allograft rejection showed markedly increased Calb and moderately increased C beta 2 mu, concurrent with decreased creatinine clearance (CCr). Five other patients (Group II) with no evidence of rejection demonstrated episodes of grossly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Other authors stated that serum β 2MG estimated GFR even more accurately compared to serum creatinine [ 15 , 20 , 21 ]. Woo et al [ 33 ] concluded that the increase of serum β 2MG concentration evidenced a glomerular pathology, which has recently been recognized as the main cause of chronic allograft dysfunction [ 6 ]. Meanwhile, observed weak correlation ( r = 0.466) between serum β 2MG and creatinine (though their sieving coefficients are close to unity [ 33 ]) suggests that another reason for the increase of serum β 2MG concentration might be transplant complications and comorbidities leading to an increase of β 2MG synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors stated that serum β 2MG estimated GFR even more accurately compared to serum creatinine [ 15 , 20 , 21 ]. Woo et al [ 33 ] concluded that the increase of serum β 2MG concentration evidenced a glomerular pathology, which has recently been recognized as the main cause of chronic allograft dysfunction [ 6 ]. Meanwhile, observed weak correlation ( r = 0.466) between serum β 2MG and creatinine (though their sieving coefficients are close to unity [ 33 ]) suggests that another reason for the increase of serum β 2MG concentration might be transplant complications and comorbidities leading to an increase of β 2MG synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum β2-МG concentration statistically correlated to lesser degree with serum creatinine concentration (r = 0.51 p < 0.05), urine β2-МG concentration (r = 0.53, p<0.05), with GFR (r = -0.44, p < 0.05), proteinuri (r = 0.50, p < 0.05) and urine density (r = -0.41, p<0.05) allowing explain its increase by glomerular RAT pathology [5] at which the filtration process undergoes changes. At the same time, very weak correlation between β2-МG and creatinine allows assume that another cause of increased blood serum β2-MG concentration in the patients with chronic RAD was the increase of its extrarenal synthesis that was found earlier by other authors [31].…”
Section: Original Articlementioning
confidence: 51%
“…Correlation analysis has shown interdependence between blood serum β2-МG and ІL-10 concentrations (r = 0.56, p < 0.05). In view of the literature data showing that β2-MG and IL-10 are secreted by the lymphocytes in the peripheral blood [1,5,11,19,31], it is possible to assume that the cause of chronic RAD in this case is antibody-mediated rejection.…”
Section: Original Articlementioning
confidence: 96%
See 2 more Smart Citations